Identitas Bekasi dalam Tiga Akun Instagram Komunitas - Rido Budiman; Fakhran Al Ramadhan (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2018)
This study aims to find out how the community Instagram social media account constructs, reminds and informs the city identity of Bekasi that "this is Bekasi" by bringing up Bekasi city landmarks in its Instagram account. In addition to being a community that explores about Bekasi, what kind of photos are selected to be displayed in the Bekasi community Instagram account. The method used in this research is ethnography, discourse analysis and also visual analysis, where the data findings will be described and then reviewed for analysis from field observations, interview processes, and literature search. The plan to be achieved in this study is to develop a study of cultural studies specifically on city studies and social media. The research sought to prove that there were city identity contests in various Instagram social media accounts that were different from the vision of the city identity that was raised by the Bekasi city government.